Do stress symptoms impact handgrip strength and firearm shooting accuracy among military police officers? - Vasconcelos Junior, Valter R.; Costa, Romulo C. T.; Oliveira, Geanderson S.; Fortes Junior, Pedro F. C.; Machado, Alexandre F.; Rica, Roberta Luksevicius; Mallett, Gregg S.; Bullo, Valentina; Bergamin, Marco; Gobbo, Stefano; Bocalini, Danilo Sales (Frontiers in Psychology, 2025)
IntroductionThe operations carried out by the Military Police (MP) in public safety and violence prevention, driven by the evolving needs of contemporary society, impose specific physical and psychological requirements on their personnel that are typically not encountered by the general population. In this context, factors such as exposure to violence, frequent risk of death, heavy workloads, challenging working conditions, and elevated stress levels associated with their missions are integral to the daily experiences of MP officers, rendering them one of the most vulnerable professional groups. Therefore, the objective of this study was to assess whether the presence of stress symptoms impacts handgrip strength and firearm shooting accuracy among MP officers.MethodsThe study included 24 third-year officer cadets stationed at the Espírito Santo Military Police Academy; all participants volunteered. Stress levels were measured using Lipp’s Inventory of Stress Symptoms (LSSI), categorizing participants into two groups: those exhibiting stress symptoms (CE, n = 11) and those without (SE, n = 13). Firearm shooting was conducted during the basic training track evaluation of Defensive Shooting in Life Preservation, employing the Giraldi Method, with shots directed at a fixed target 5 meters away. Key metrics evaluated included the time taken to execute the shots (T), total score (TS), and shooting accuracy calculated as (50 x TS/T). Handgrip strength (HGS) was measured in the dominant hand (DH), non-dominant hand (NDH), and shooting position (SP) using a handgrip dynamometer.ResultsThe average age of participants was 31.13 ± 2.49 years, with an average length of service of 7.71 ± 3.75 years and an average body mass index (BMI) of 25.58 ± 2.45 kg/m2. No significant differences (p > 0.05) were observed between groups concerning the variables T (CE: 63.45 ± 9.09, SE: 65.69 ± 9.09), TS (CE: 9.36 ± 1.03, SE: 9.38 ± 1.04), TS/T (CE: 7.47 ± 1.11, SE: 7.25 ± 1.14), DH (CE: 35.66 ± 8.29, SE: 38.54 ± 6.88), and NDH (CE: 34.19 ± 6.48, SE: 37.39 ± 8.56). However, significant differences (p < 0.05) were identified between the groups regarding the SP parameter (CE: 39.96 ± 10.40, SE: 47.06 ± 8.57).DiscussionThe findings of this study indicate that, although the presence of stress symptoms led to variations in HGS during shooting position, it did not significantly impact shooting accuracy among MP cadets.